Prevalence of Diabetes by Race and Ethnicity in the United States, 2011-2016 - Cheng, Yiling J; Kanaya, Alka M; Araneta, Maria Rosario G; Saydah, Sharon H; Kahn, Henry S; Gregg, Edward W; Fujimoto, Wilfred Y; Imperatore, Giuseppina (JAMA : the journal of the American Medical Association, 2019)
The prevalence of diabetes among Hispanic and Asian American subpopulations in the United States is unknown. To estimate racial/ethnic differences in the prevalence of diabetes among US adults 20 years or older by major race/ethnicity groups and selected Hispanic and non-Hispanic Asian subpopulations. National Health and Nutrition Examination Surveys, 2011-2016, cross-sectional samples representing the noninstitutionalized, civilian, US population. The sample included adults 20 years or older who had self-reported diagnosed diabetes during the interview or measurements of hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), and 2-hour plasma glucose (2hPG). Race/ethnicity groups: non-Hispanic white, non-Hispanic black, Hispanic and Hispanic subgroups (Mexican, Puerto Rican, Cuban/Dominican, Central American, and South American), non-Hispanic Asian and non-Hispanic Asian subgroups (East, South, and Southeast Asian), and non-Hispanic other. Diagnosed diabetes was based on self-reported prior diagnosis. Undiagnosed diabetes was defined as HbA1c 6.5% or greater, FPG 126 mg/dL or greater, or 2hPG 200 mg/dL or greater in participants without diagnosed diabetes. Total diabetes was defined as diagnosed or undiagnosed diabetes. The study sample included 7575 US adults (mean age, 47.5 years; 52% women; 2866 [65%] non-Hispanic white, 1636 [11%] non-Hispanic black, 1952 [15%] Hispanic, 909 [6%] non-Hispanic Asian, and 212 [3%] non-Hispanic other). A total of 2266 individuals had diagnosed diabetes; 377 had undiagnosed diabetes. Weighted age- and sex-adjusted prevalence of total diabetes was 12.1% (95% CI, 11.0%-13.4%) for non-Hispanic white, 20.4% (95% CI, 18.8%-22.1%) for non-Hispanic black, 22.1% (95% CI, 19.6%-24.7%) for Hispanic, and 19.1% (95% CI, 16.0%-22.1%) for non-Hispanic Asian adults (overall P < .001). Among Hispanic adults, the prevalence of total diabetes was 24.6% (95% CI, 21.6%-27.6%) for Mexican, 21.7% (95% CI, 14.6%-28.8%) for Puerto Rican, 20.5% (95% CI, 13.7%-27.3%) for Cuban/Dominican, 19.3% (95% CI, 12.4%-26.1%) for Central American, and 12.3% (95% CI, 8.5%-16.2%) for South American subgroups (overall P < .001). Among non-Hispanic Asian adults, the prevalence of total diabetes was 14.0% (95% CI, 9.5%-18.4%) for East Asian, 23.3% (95% CI, 15.6%-30.9%) for South Asian, and 22.4% (95% CI, 15.9%-28.9%) for Southeast Asian subgroups (overall P = .02). The prevalence of undiagnosed diabetes was 3.9% (95% CI, 3.0%-4.8%) for non-Hispanic white, 5.2% (95% CI, 3.9%-6.4%) for non-Hispanic black, 7.5% (95% CI, 5.9%-9.1%) for Hispanic, and 7.5% (95% CI, 4.9%-10.0%) for non-Hispanic Asian adults (overall P < .001). In this nationally representative survey of US adults from 2011 to 2016, the prevalence of diabetes and undiagnosed diabetes varied by race/ethnicity and among subgroups identified within the Hispanic and non-Hispanic Asian populations.